The management of refractory coeliac disease - Woodward, Jeremy (SAGE Publications, 2013)
A significant proportion of patients with coeliac disease are ‘nonresponsive’ to gluten withdrawal. Most cases of nonresponsive coeliac disease are due to persisting gluten ingestion. Refractory coeliac disease (RCD) is currently defined by persistent symptoms and signs of malabsorption after gluten exclusion for 12 months with ongoing intestinal villous atrophy. Primary (without initial response to diet) and secondary (relapse following response to diet) RCD is recognized. RCD is further classified as type I or type II based on the absence or presence of a population of aberrant intestinal lymphocytes. Quality of dietetic advice and support is fundamental, and lack of objective corroboration of gluten exclusion may result in over-identification of RCD I, particularly in those cases with persisting antibody responses. Over-reliance on lymphocyte clonality similarly may result in over-diagnosis of RCD II which requires careful quantification of aberrant lymphocyte populations. Management of RCD should be undertaken in specialist centres. It requires initial intensive dietary supervision, strict gluten exclusion and subsequent re-evaluation. There is currently insufficient evidence to recommend specific treatments. Steroids are often used in both RCD I and II (albeit with little objective evidence of benefit in RCD II), and azathioprine as steroid-sparing therapy in RCD I. There is growing evidence for the use of cladribine in RCD II with autologous stem cell transplantation in nonresponders, but this requires further multicentre evaluation. There remains considerable controversy regarding the diagnosis, treatment and surveillance of RCD: international consensus in these areas is urgently required to facilitate future therapeutic advances.